Mobile phones in clinical practice: reducing the risk of bacterial contamination. Issue 9 (18th May 2014) - Mark, D.; Leonard, C.; Breen, H.; Graydon, R.; O'Gorman, C.; Kirk, S.
Summary Background Mobile smart phones have become increasingly integrated into the practice of doctors and allied medical professionals. Recent studies suggest them to represent reservoirs for pathogens with potential to cause nosocomial infections. This study aimed to investigate the level of contamination on phones used on surgical wards and identify strategies for their safe use within clinical areas. Methods Fifty mobile phones were taken from members of the multidisciplinary team working in a surgical unit. Phones were swabbed by two trained investigators using a standardised technique and samples streaked out using an automated specimen inoculator onto two types of culture media (Columbia blood agar and MacConkey agar). Colonies were identified and counted by a single trained investigator in a blinded fashion. Simultaneously a questionnaire investigating usage levels of phones was given to 150 healthcare workers. Results Sixty per cent of phones sampled had some form of contaminant isolated from their phone. Thirty‐one (62%) of phones had only three colonies or less isolated on medium. No pathogenic or drug resistant strains of bacteria were identified. A total of 88% of individuals sampled by questionnaire used their phone within the workplace of which 55% used it for clinical purposes. Sixty‐three per cent expected there to be some form of contaminant on their phone with only 37% admitting to cleaning it regularly. Seventy‐five per cent of people did not view a ban on phones as a practical solution was they found to be an infection risk. Conclusion Touch screen smart phones may be used safely in a clinical environment, with a low risk of cross‐contamination of nosocomial bacteria to patients, in the setting of effective adherence to hand hygiene policies.